Biochemical and physiological responses induced in Mytilus galloprovincialis after a chronic exposure to salicylic acid - Freitas, Rosa (2020)
A vast variety of substances currently reaches the aquatic environment, including newly developed chemicals and products. Lack of appropriate analytical methods for trace determinations in aquatic ecosystem compartments and lack of information regarding their toxicity explains existing regulation gaps. However, suspicion of their toxicity assigned them as Contaminants of Emerging Concern (CECs). Among CECs are Pharmaceuticals including Salicylic Acid (SA), which is the active metabolite of acetylsalicylic acid (ASA; aspirin). The aim of the present study was to evaluate the potential effects of SA on the mussel Mytilus galloprovincialis. For this, organisms were exposed for 28 days to different concentrations of SA (0.005; 0.05; 0.5 and 5 mg/L), resembling low to highly polluted sites, after which different physiological and biochemical parameters were evaluated to assess organism’s respiration rate, neurotoxic, metabolic and oxidative stress status. Our results clearly showed that SA strongly reduced the respiration capacity of mussels. Also, SA inhibited the activity of superoxide dismutase (SOD) and catalase (CAT) enzymes, but increased the activity of glutathione peroxidase (GPx) and glutathione-S-transferases (GSTs), which prevented the occurrence of lipid peroxidation (LPO). Nevertheless, oxidative stress was confirmed by the strong decrease of the ratio between reduce glutathione (GSH) and oxidized (GSSG) glutathione in contaminated mussels. Moreover, neurotoxicity was observed in mussels exposed to SA. Overall, this study demonstrates the metabolic, neurotoxic and oxidative stress impacts of SA in M. galloprovincialis, which may result in negative consequences at the population level.